Asesmen Autentik Analisis Butir Soal Dengan Rasch Model Di Sekolah Dasar: Literature Review - Indri Pudjiati; Faisal Madani (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
Authentic assessment is an assessment that measures competence in the cognitive (knowledge), affective (attitude), and psychomotor (skills) domains of learners, not only conceptual understanding but also the ability to apply concepts and theories in real or test practical skills in a particular field. The purpose of this study is to present the latest data, evaluate, and describe the authentic assessment of item analysis with the Rasch model in elementary school. The research method used in this study is a literature review with Narrative Literature Review (NLR) model with Compare technique. The findings obtained from this study can be concluded that the teachers in elementary schools have routinely conducted authentic assessments in analyzing the problem items either manually or with the help of applications. Rasch model is one of the ways that can facilitate the work of teachers in analyzing problem items. This study implies that in the future rasch model can be developed with a way of working that is easier to use for teachers.